Covert affairs. Season one [videorecording (DVD)] - Corman, Matt, 1971-; Ord, Chris (Universal Studios Home Entertainment, 2011)
Meet Annie Walker: smart, stunning, and the CIA's newest field operative in one of their most secretive branches. Suddenly summoned by headquarters for active duty one month before training is over, she's quickly thrown into a shadowy world full of cons, killers, and international crime rings. What she doesn't know is there's something - or someone - from her past that her bosses want badly enough to put her in harm's way.